A novel framework for Detecting Breast Cancer, Brain Tumor & Pneumonia Using Deep Learning Techniques - K V Daya Sagar (Journal of Informatics Education and Research, 2024)
Brain tumours, breast cancer, and pneumonia are significant diseases causing a substantial number of deaths globally. These diseases affect a great part of the world, including India. Research on early detection strategies is critical for saving lives. This proposal describes a unique way to use deep learning approaches to detect three common diseases: breast cancer, brain tumours, and pneumonia. This approach aims to improve treatment outcomes and diagnostic accuracy by integrating a range of medical imaging modalities tailored to individual diseases. In similar challenges, DCNNs have demonstrated remarkable speed and accuracy, demonstrating their potential to enhance medical diagnosis. DCNN models can help medical professionals by providing accurate and automated illness identification, especially for areas with a shortage of radiologists.